(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The revolutions in information technology and hyper-connectivity have profoundly changed the way citizens interact with governments worldwide. The challenges encountered in e-government implementations highlight the absence of a cohesive understanding of e-government as a field. This study introduces a comprehensive and unified conceptual framework for e-government, supported by extensive qualitative research, to outline the essential factors for successful e-government implementation. Through 168 detailed interviews with various stakeholders in India, the study characterizes e-government as a multidimensional concept with key components including customer orientation, channel orientation, and technology orientation. Building on theories of customer orientation and relationship marketing, the study identifies citizen orientation as the most crucial factor for successful e-government projects, followed by channel and technology orientations. It also examines the roles of the digital divide, economic growth, and political stability as moderators in e-government. Additionally, the study explores both tangible and intangible outcomes of e-government, with perceived privacy and shared understanding as moderating factors. The research concludes with theoretical and practical implications and suggestions for future studies.